Some Physical and Chemical Characteristics of some "gardud" Soils in the State pf North Kordofan, Sudan - I. Adam, Adam; A. Elsunni, Mai (Gezira Journal of Agricultural Science; Vol 1 No 2 (2003), 2021)
Four locations south of Elobied town in the State of North Kordofan were selected to represent three "gardud" soils in May-June 1996. These locations were Aradayia, Umood, Bangadeed and Kaba. The results of the study showed that the soils are genetically young and are, therefore classified as Entisols and Inceptisols. The soil at Kaba is coarse loamy and those at Umood, Aradayia and Bangadeed are fine loamy. Kaolinite is the dominant clay type of the soil at Kaba, whereas smectites dominate the other three soils. The soil at Kaba is conceived to be formed in situ from sandstone as substantiated by grain-size. distribution, while the other three soils are of alluvial origin. The compactness of the soils at Aradayia, Umood, and Bangadeed is seen as a result of cementation of coarse soil separates by smectitic clays, whereas that of the soil at Kaba is envisaged as cementation by iron oxides. The soils at Aradayia, Umood, and Bangadeed are moderately fertile, whereas that at Kaba is infertile. The former three soils can be utilized under judicious cultural practices that increase soil permeability for rain water, lessen erosion hazard, and conserve soil moisture, in addition to rational application of nitrogen fertilizers. The "gardud" soils at Aradayia, Umood and Bangadeed have promising potential for field crops suited to the prevalent climate in the area, whereas the "gardud" soil at Kaba is best suited for natural grazing and tree crops, i.e., Acacia senegal (Hashab).